ANALYSIS OF THE IMPLEMENTATION OF THE REGIONAL SECRETARIAT'S FUNCTIONS IN THE FORMULATION OF THE FREE NUTRITIOUS MEALS PROGRAM POLICY IN KUBU RAYA REGENCY - Ade Risna Sari; Fitriani; Khairul Radit Pramudya; Sugino (INJOSEDU: International Journal of Social and Education, 2025)
This study aims to analyse the implementation of the duties and functions of the Regional Secretariat in formulating the Free Nutritious Meal Programme policy in Kubu Raya District. The Free Nutritious Meals Programme is a strategic policy of the Kubu Raya District Government in an effort to improve nutritional quality and support the continuity of education for primary and secondary school students, as well as reduce stunting. The Regional Secretariat of Kubu Raya District, as the head of the Free Nutritious Meals Programme task force, has strategic duties and functions in planning, organising, mobilising and controlling the Free Nutritious Meals Programme in Kubu Raya District. Researchers used the POAC (Planning, Organising, Actuating, Controlling) management theory as an analytical tool. The research method used was descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation of informants consisting of Regional Secretariat officials, relevant regional apparatus, and programme supporters. This study concludes that the implementation of the Regional Secretariat's duties in formulating the Free Nutritious Meals Programme policy in Kubu Raya Regency has been carried out in accordance with the principles of POAC management. However, there is still a need to strengthen coordination with regional work units (SKPD) and third parties, namely the Nutrition Fulfilment Service Unit (SPPG), supervision, and capacity building for officials so that the policy can be implemented more effectively and sustainably.